(untitled) - V. Magezi (Acta Theologica)
As a sub-focus area of African theology, “Pastoral care in Africa” has been discussed considerably since the beginning of the post-colonial period in the 1960s. However, few scholars have articulated a definitional framework. Therefore, the ontological question: What is pastoral care in Africa? is worth posing to understand its “being”. This article locates the discussion of pastoral care in Africa within the rising trend of creative theologies that emerged after colonisation. The article proceeds by framing the context of pastoral care in Africa, followed by describing the undergirding presuppositions to caregiving in Africa. Then the article advances a definition of pastoral care in Africa, which is followed by a discussion about the elements that demarcate it. The article concludes by proposing “relationality, participation, presence, consultation, joint exploration and collective decisionmaking, cooperation, and contribution” as critical principles that emerge from the conceptual definition of pastoral care in Africa for effective caregiving.